Association of the quality of interpersonal care during family planning counseling with contraceptive use - Dehlendorf, Christine; Henderson, Jillian T.; Vittinghoff, Eric; Grumbach, Kevin; Levy, Kira; Schmittdiel, Julie; Lee, Jennifer; Schillinger, Dean; Steinauer, Jody (American journal of obstetrics and gynecology, 2016)
Health communication and interpersonal skills are increasingly emphasized in the measurement of health care quality, yet there is limited research on the association of interpersonal care with health outcomes. As approximately 50% of pregnancies in the United States are unintended, whether interpersonal communication influences contraceptive use is of public health importance. The aim of this study was to determine whether the quality of interpersonal care during contraceptive counseling is associated with contraceptive use over time. The Patient–Provider Communication about Contraception study is a prospective cohort study of 348 English-speaking women seen for contraceptive care, conducted between 2009 and 2012 in the San Francisco Bay Area. Quality of communication was assessed using a patient-reported interpersonal quality in family planning care measure based on the dimensions of patient-centered care. In addition, the clinical visit was audio recorded and its content coded according to the validated Four Habits Coding Scheme to assess interpersonal communication behaviors of clinicians. The outcome measures were 6-month continuation of the selected contraceptive method and use of a highly or moderately effective method at 6 months. Results were analyzed using mixed effect logistic regression models controlling for patient demographics, the clinic and the provider at which the visit occurred, and the method selected. Patient participants had a mean age of 26.8 years (SD 6.9 years); 46% were white, 26% Latina, and 28% black. Almost two-thirds of participants had an income of <200% of the Federal Poverty Level. Most of the women (73%) were making visits to a provider whom they had not seen before. Of the patient participants, 41% were still using their chosen contraceptive method at 6-month follow-up. Patients who reported high interpersonal quality of family planning care were more likely to maintain use of their chosen contraceptive method (adjusted odds ratio [aOR], 1.8; 95% CI, 1.1–3.0) and to be using a highly or moderately effective method at 6 months (aOR, 2.0; 95% CI, 1.2–3.5). In addition, 2 of the Four Habits were associated with contraceptive continuation; “invests in the beginning” (aOR, 2.3; 95% CI, 1.2–4.3) and “elicits the patient’s perspective” (aOR, 1.8; 95% CI, 1.0–3.2). Our study provides evidence that the quality of interpersonal care, measured using both patient report and observation of provider behaviors, influences contraceptive use. These results provide support for ongoing attention to interpersonal communication as an important aspect of health care quality. The associations of establishing rapport and eliciting the patient perspective with contraceptive continuation are suggestive of areas of focus for provider communication skills training for contraceptive care.